A Perfect Storm: Crack Cocaine, HSV-2, and HIV Among Non-Injecting Drug Users in New York City. (7th June 2014) - Des Jarlais, Don C.; McKnight, Courtney; Arasteh, Kamyar; Feelemyer, Jonathan; Perlman, David C.; Hagan, Holly; Dauria, Emily F.; Cooper, Hannah L.F.
Abstract : Prevalence of human immunodeficiency virus (HIV) infection has reached 16% among non-injecting drug users (NIDU) in New York City, an unusually high prevalence for a predominantly heterosexual population that does not inject drugs. Using a long-term study (1983–2011, >7, 000 subjects) among persons entering the Beth Israel drug-treatment programs in New York City, we identified factors that contributed to this high prevalence: a preexisting HIV epidemic among injectors, a crack cocaine epidemic, mixing between injectors and crack users, policy responses not centered on public health, and herpes-simplex virus 2 facilitating HIV transmission. Implications for avoiding high prevalence among NIDU in other areas are discussed.